Understanding the motivations, needs, and challenges faced by aspiring neurosurgeons in Africa: an E-survey. (2nd January 2022) - Kanmounye, Ulrick Sidney; Zolo, Yvan; Tsopmene, Marvin Richie Dongmo; Nguembu, Stéphane; Ndajiwo, Aliyu Baba; Abdifatah, Khalif; Sichimba, Dawin; Sallah, Aminata Yandeh; Endalle, Geneviève; Kaduyu, Robert; Chege, Kennedy Kimani; Takoukam, Régis; et al.
Abstract: Introduction: Three million African patients need a neurosurgical consultation every year, but there are not enough neurosurgeons to meet this need. Efforts have been made to increase the neurosurgical capacity through the creation of training programs in Africa. Although these programs have been successful, there is still a long way to go. Aspiring African neurosurgeons (AANs) will become neurosurgeons in the future if they are given the resources and opportunities. The authors set out to understand the perceptions, needs, and difficulties faced by AANs. Methods: An e-survey containing 45 questions was created using Google Forms and distributed via social media. The survey was anonymous, and it was distributed from June 2, 2020, to June 16, 2020. Summary descriptive statistics and the Chi-Square test were calculated. The p -value was considered to be significant below .05. Results: A total of 221 AANs aged 23.5 ± 3.3 years and from 22 African countries responded to the survey. Most were male (66.1%) and medical students (84.6%). Few had assisted a neurosurgical intervention in-person (24.9%), had a mentor (29.0%) or attended a journal club (10.3%). A small proportion was unwilling to train in their home country (19.5%) or a neighboring country (16.3%). The top three reasons for choosing neurosurgery were prestige, advice from a family member, and projected income. Also, respondents felt neurosurgery was expensive. Conclusion: AANs are passionate about neurosurgery but lack the information, guidance, or opportunities to fulfil their wish.